System level simulation for distributed antenna system - Huq, K.M.S.
Distributed antenna system (DAS) constitutes one of the most fascinating schemes to efficiently achieve the rigorous quality of service demands of next generation wireless networks. System level simulation (SLS) approach is considered since things are too complicated to be dealt only analytically and it would not be cost-effective to deploy all the real scenario to test every feature.In this paper, we investigated Multiple-input-Single-output (MISO) assisted transmission technique used in DAS. The performance of downlink multi-cell DAS in terms of capacity improvement using SINR for MISO transmission scheme is examined. A SLS tool is used to analyze the performance of DAS.